The functions and applications of organoids in rheumatic immune diseases - Huaijuan Huang; Aimin Yan; Hesong Wang; Heng Xu; Ruhang Li; Kai Yuan; Guangrui Huang (KeAi Communications Co., Ltd., 2024)
Rheumatic immune disorders are a group of conditions that affect the immune system, leading to various clinical symptoms. These diseases can cause pain, reduce the quality of life, and increase the risk of death in severe cases. Diagnosis and treatment are very complex due to the different types of disease and individual differences and the unknown pathogenesis of the disease. Further research is necessary to provide new clues for disease treatment. Organoid technology that makes up for the shortcomings of animal model species differences can better simulate disease onset mechanisms than animal models. It can be used as a screening platform for new therapeutic targets, as well as personalized settings based on patient-derived organoids, promising as an effective tool for the study of rheumatic immune diseases. Therefore, the article summarizes studies related to organoids and their application in rheumatic immune diseases. It also provides an outlook on the potential of organoids in this field and discusses the challenges that need to be addressed, putting new ideas for future research on these diseases.